2018
DOI: 10.1177/1177932218755337
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Informatic Analysis and Design of Peptide Vaccine From Multi-epitopes Against Corynebacterium pseudotuberculosis

Abstract: Caseous lymphadenitis (CLA) is a disease caused by Corynebacterium pseudotuberculosis bacteria that affects sheep and goats. The absence of a serologic diagnose is a factor that contributes for the disease dissemination, and due to the formation of granuloma, the treatment is very expensive. Therefore, prophylaxis is the approach with best cost-benefit relation; however, it still lacks an effective vaccine. In this sense, this work seeks to apply bioinformatic tools to design an effective vaccine against CLA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 101 publications
1
40
0
3
Order By: Relevance
“…Currently available diagnostic tools provide limited efficacy. Recent analysis of the C. pseudotuberculosis pangenome allowed the discovery of new bacterial proteins presenting B‐cell epitopes (Santana‐Jorge et al ., ), and another study provided new insights in the use of the CP40 protein as an immunogenic through bioinformatics analysis (Droppa‐Almeida et al ., ). By employing some of these newly discovered antigens in the development of immunoenzymatic assays, the present work demonstrated that several of these molecules are broadly recognized by the host immune system and thus can be used to support accurate immunodiagnostic assays.…”
Section: Discussionmentioning
confidence: 97%
“…Currently available diagnostic tools provide limited efficacy. Recent analysis of the C. pseudotuberculosis pangenome allowed the discovery of new bacterial proteins presenting B‐cell epitopes (Santana‐Jorge et al ., ), and another study provided new insights in the use of the CP40 protein as an immunogenic through bioinformatics analysis (Droppa‐Almeida et al ., ). By employing some of these newly discovered antigens in the development of immunoenzymatic assays, the present work demonstrated that several of these molecules are broadly recognized by the host immune system and thus can be used to support accurate immunodiagnostic assays.…”
Section: Discussionmentioning
confidence: 97%
“…Although, there was no major difference between predicted antigenicity values for probable vaccine candidate proteins, S protein was selected as a better vaccine candidate protein compared to others depending on in silico analyses results. Physico-chemical analysis showed that S protein had a negative GRAVY value indicating that S protein is hydrophilic and has a better interaction with surrounding water molecules 36 . Also, it had stable and soluble characteristics which are important parameters for biophysical studies on epitope-based vaccine design.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a small number of these may be required to induce protective immunity [25,26]. Computational modelling has provided a powerful tool for locating and mapping the conformation of immunogenic epitopes within proteins [27,28]. This has led to interest in peptidebased vaccines [25].…”
Section: Conjugate Vaccinesmentioning
confidence: 99%
“…However, antigenic epitopes on a protein are not simply a sequence of amino acids, as the peptides used must mimic the conformation of the immunogenic epitope within the native protein. Computational modelling has provided a powerful tool for locating and mapping the conformation of immunogenic epitopes within proteins [27,28].…”
Section: Conjugate Vaccinesmentioning
confidence: 99%